The value of tourism public opinion management in social governance: A study on the impact of electronic word-of-mouth perception on people’s livelihood well-being - Li, Xiuxiang; Wu, Yingqi; Jiang, Yi (Frontiers in Psychology, 2022)
In the process of tourism market upgrading and tourism iteration, tourism companies will face a more complex public opinion environment. Designing a socialized public opinion management method for tourism with social governance to improve people’s livelihood and well-being has become the primary concern of the tourism industry. Therefore, the existing literature has extensively focused on the role and influence of public opinion word of mouth from the perspective of tourist or consumer behavior. However, moderating role of individual tourist characteristics and environmental elements has not yet been deeply explored. Therefore, integrating with the background of the social media, this study examines how electronic word-of-mouth (eWOM) is related to the well-being of people’s livelihood, and explores the interaction between individual characteristics and eWOM perception in Study 1. Furthermore, in Study 2, we provided novel boundary conditions, namely environmental elements (i.e., physical, social and historical environment). We used mixed methods (i.e., quantitative and experimental designs) to reveal that tourists’ perceptions of eWOM have a significant positive effect on tourists’ well-being experience. The results show that tourists’ eWOM perception has a significant positive impact on their well-being experience. In addition, individual characteristics and environmental elements showed significant moderating effects between eWOM and well-being of people’s livelihood. This study discusses the theoretical and practical implications, exploring the value of tourism public opinion management in social governance centered on tourists’ eWOM perception, which helps tourism companies to effectively prevent and resolve risks affecting social harmony and stability in the field of cultural tourism and create a safe and stable cultural tourism market environment.